New Business Analysis of Record Document and Management System - Perdana, Ariabima Putra; Syahputra, Syahputra; Pradana, Mahir (P3KM Politeknik Pertanian Negeri Samarinda, 2023)
This research aims to analyze the new business owned by the company PT Infomedia Nusantara. This research uses the 8P theory (Product, Price, Place, Promotion, People, Process, Physical evidence, Public Relations). Apart from that, RDMS is claimed to be a technology that contributes to the environment. It cannot be denied that the large number of documents in physical form is sometimes difficult for companies to manage properly. Understanding this need, Infomedia, which is known as a subsidiary of Telkom Indonesia (Telkom), offers a Record Document Management System based service called ProVue-RDMS. This service complements the back end process solution that Infomedia offers as one of the main services to customers. Document management is one element of company information management which has a management period of up to decades. The purpose of using this 8P theory is to make the results of this research more comprehensive and also more flexible. The aim of document management is to make it easier for companies or organizations to access, share and collaborate on their documents, while increasing efficiency and reducing the risk of files being lost or damaged.